Analysing the Compensatory Properties of the Outranking Approach PROMETHEE - Sebastian Schär; Erik Pohl; Jutta Geldermann (Journal of Multi-Criteria Decision Analysis, 2025)
The PROMETHEE methods are increasingly applied in environmental and public policy decision-making due to their comprehensiveness and explainability. However, the literature contains differing statements regarding their compensatory properties. Compensation in multiple criteria decision aggregation procedures is commonly understood as allowing a gain in one criterion to offset a loss in another one. In certain domains, such as environmental or public policy decision-making, it may be undesirable, as some impacts may result in losses too severe to be counterbalanced by good performance on other criteria. Therefore, it may be necessary to limit the extent to which an aggregation procedure permits compensation or to explicitly control it as needed. Guidelines and detailed analytical tools, however, that help users and analysts to control compensation in the PROMETHEE methods remain scarce and often lack transparency. In this study, we analyse the compensatory behaviour of the PROMETHEE I and II methods and identify the key determinants for compensation in these methods. Based on these insights, we develop flow insensitivity intervals to assess the sensitivity of a given decision model towards compensatory effects and provide a set of general guidelines for controlling compensation in the PROMETHEE I and II methods for any given pair of criteria. The findings are illustrated at hand of an environmental management case study. By combining the guidelines with flow insensitivity intervals, users and analysts gain access to measures of varying granularity to evaluate and control compensation in a PROMETHEE decision model.
Keywords: 300; compensation; multiple criteria decision analysis; outranking; PROMETHEE